BAD modulates counterregulatory responses to hypoglycemia and protective glucoprivic feeding. - Mayowa A Osundiji; Marina L Godes; Mark L Evans; Nika N Danial (PLoS ONE)
Hypoglycemia or glucoprivation triggers protective hormonal counterregulatory and feeding responses to aid the restoration of normoglycemia. Increasing evidence suggests pertinent roles for the brain in sensing glucoprivation and mediating counterregulation, however, the precise nature of the metabolic signals and molecular mediators linking central glucose sensing to effector functions are not fully understood. Here, we demonstrate that protective hormonal and feeding responses to hypoglycemia are regulated by BAD, a BCL-2 family protein with dual functions in apoptosis and metabolism. BAD-deficient mice display impaired glycemic and hormonal counterregulatory responses to systemic glucoprivation induced by 2-deoxy-D-glucose. BAD is also required for proper counterregulatory responses to insulin-induced hypoglycemia as evident from significantly higher glucose infusion rates and lower plasma epinephrine levels during hyperinsulinemic hypoglycemic clamps. Importantly, RNA interference-mediated acute knockdown of Bad in the brain provided independent genetic evidence for its relevance in central glucose sensing and proper neurohumoral responses to glucoprivation. Moreover, BAD deficiency is associated with impaired glucoprivic feeding, suggesting that its role in adaptive responses to hypoglycemia extends beyond hormonal responses to regulation of feeding behavior. Together, these data indicate a previously unappreciated role for BAD in the control of central glucose sensing.